1997
DOI: 10.1007/bf02737751
|View full text |Cite
|
Sign up to set email alerts
|

Children poisoning in Taiwan

Abstract: Poisoning is a well known cause of morbidity and mortality in children. In Taiwan, little information has been published regarding the status of pediatric poisoning exposures. To provide more information on pediatric poisoning exposures for the purpose of poison prevention, a retrospective study was designed and conducted to analyse the data of National Poison Centre (NPC), Taiwan. All telephone inquiries concerning poisoning exposures in those under 19 years of age, received by NPC-Taiwan from July 1985 throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
31
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 19 publications
6
31
0
Order By: Relevance
“…The finding of more poisoning episodes in children under five years old was similarly reported in Nigeria and Taiwan province, China. [9,10] Other epidemiological studies of pediatric poisoning have demonstrated that the most common risk factors for poison exposure are young age and female gender, which are in agreement with our fi ndings. [11][12][13][14][15][16][17] Poisoning incidents can be categorized into intentional or unintentional types based on how they happened, but most of childhood poisonings are accidental in nature.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The finding of more poisoning episodes in children under five years old was similarly reported in Nigeria and Taiwan province, China. [9,10] Other epidemiological studies of pediatric poisoning have demonstrated that the most common risk factors for poison exposure are young age and female gender, which are in agreement with our fi ndings. [11][12][13][14][15][16][17] Poisoning incidents can be categorized into intentional or unintentional types based on how they happened, but most of childhood poisonings are accidental in nature.…”
Section: Discussionsupporting
confidence: 92%
“…[9,10] This difference might be explained by the differences in study design and socio-cultural values. The finding of more poisoning episodes in children under five years old was similarly reported in Nigeria and Taiwan province, China.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is very likely that this reporting is an underestimate of the actual magnitude of this problem as many cases go unreported. 6 Various studies from India and abroad show that childhood poisoning is more common in males and similar pattern was observed in the present study (4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Children between 1-3 yr were most commonly involved in the present study, a pattern consistent with most of the other studies, 4-6, 12 a notable exception being Japan where infants are most commonly involved.…”
Section: Discussionsupporting
confidence: 90%
“…The abuse of psychoactive drugs from the phenylethylamine and phenylisopropylamine groups has become a very serious social problem in Taiwan over the last decade. [9][10][11][12][13][14][15][16][17][18][19][20][21][22] Unknown drugs are typically detected and identified by gas chromatography-mass spectrometry (GC-MS) because this approach is highly sensitive and can separate organic compounds in complex mixtures. [23][24][25][26] The compounds are often derivatized on the amine to yield more specific fragmentation information.…”
Section: Introductionmentioning
confidence: 99%